Columnar Grain Size Effect on Cross-Plane Conductivity of Yttria-Stabilized Zirconia Thin Films. Issue 9 (14th June 2018) - Park, Jung Hoon; Ahn, Junsung; Yoon, Kyung Joong; Kim, Hyoungchul; Ji, Ho-Il; Lee, Jong-Ho; Han, Seung Min; Son, Ji-Won
Abstract : Thin films of yttria-stabilized zirconia (Y2 O3 -stabilized ZrO2, YSZ) with various columnar grain sizes are successfully fabricated by combining a post-annealed seed layer and a successively deposited effective layer by pulsed laser deposition (PLD). As a result, YSZ thin films of different columnar grain sizes (column diameters of ∼15 nm, ∼40 nm, and ∼190 nm) are obtained with identical fabrication parameters except for the seed layer to engineer the grain size. According to analyses of the physical properties, the variation in the grain size induces differences not only in the grain boundary density, but also the strain state in each sample. These changes in physical properties are considered to affect the electrical property of the thin films in a combined way. Measurements of the cross-plane electrical conductivities of the YSZ thin films reveal that the electrical conductivity of the YSZ thin film increases up to 2 times as the columnar grain size increases. The present study provides intelligent and effective method for the design and manipulation of the microstructure of oxide thin films, thus enabling investigations into the correlated properties of interest.